Primary cutaneous γδ T‐cell lymphoma with unusual immunophenotype: A case report and review of published work. Issue 3 (7th January 2020) - Kamijo, Hiroaki; Miyagaki, Tomomitsu; Norimatsu, Yurie; Awaji, Kentaro; Oka, Tomonori; Suga, Hiraku; Sugaya, Makoto; Sato, Shinichi
Abstract: Primary cutaneous γδ T‐cell lymphoma (CGD‐TCL) is a rare form of primary cutaneous lymphoma. The histopathological features of CGD‐TCL are still unclear because of its rarity. Here, we report a case of a 77‐year‐old Japanese man who presented with a 9‐month history of erythematous plaques on his left forearm. Skin biopsy specimens revealed the infiltration of atypical medium/large‐sized lymphocytes from the epidermis to the deep dermis. Atypical lymphocytes were positive for CD3, CD5, CD8 and Vδ1, and negative for CD4, CD7, CD56, EBER‐ISH, intracellular antigen‐1, granzyme B and perforin. CD30 was partially expressed. We also reviewed 246 cases of CGD‐TCL from the published work. CD4 − CD8 − double‐negative cases were 113 of 196 cases (57.6%), followed by CD4 − CD8 + cases (52/196, 26.5%). CD5 was expressed in 25.8% of the cases (34/132). At least one cytotoxic molecule marker was expressed in 150 of 160 cases (93.8%). Some cases showed an indolent clinical course, especially in mycosis fungoides‐like CGD‐TCL cases. CD5 positivity and lack of cytotoxic molecule expression could be associated with a better prognosis. In addition, CD30 expression was found in approximately half of CGD‐TCL cases (51/112 cases), suggesting that brentuximab vedotin could be a good treatment option for such patients. Further studies with more cases with detailed clinical and pathological information are necessary to elucidate the etiology and prognostic markers of this entity.